An Unusual Mass of Posterior Mediastinum: A Case of Retrotracheal Parathyroid Adenoma Presenting With Primary Hyperparathyroidism. Issue 12 (November 2018) - Rabiou, Sani; Efared, Boubacar; Aminou, Sani; Harmouchi, Hicham; Sidibé, Kassim; Lakranbi, Marouane; Ouadnouni, Yassine; Smahi, Mohamed
Although parathyroid ectopy in the mediastinum has been the subject of several publications, its location in the posterior mediastinum is very rarely reported. We report a case of a 69-year-old patient who presented with clinical symptoms of malignant hypercalcemia due to a retrotracheal mediastinal parathyroid adenoma. The surgical excision leads to a quick normalisation of the phosphocalcic balance with improvement of the clinical symptoms. Ectopic hypersecreting parathyroid adenoma with life-threatening hypercalcemia should prompt radiological assessment and appropriate surgical management to prevent further clinical complications.